Penerapan model pembelajaran project based learning untuk meningkatkan kreativitas peserta didik pada pembelajaran ipa tema 8 lingkungan sahabat kita kelas 5 sekolah dasar - Dhita Amaliya; Peduk Rintayati; Chumdari Chumdari (Didaktika Dwija Indria, 2023)
The study's goals were to: 1) explain how project-based learning can help students become more creative when studying Science Theme 8: Our Friends' Environment; and 2) use project-based learning to help students become more creative when studying Science Theme 8: Neighborhood of Our Friends. This kind of inquiry is called class action. In order to gather information, researchers used observation, interviews, product originality evaluations, and document reviews. To verify the accuracy of the data, researchers utilized source triangulation and technique triangulation. Techniques for data reduction, data visualization, and inference were employed to evaluate the outcomes. The study's findings indicate that project-based learning in the classroom can help pupils become more creative. Student originality for Cycle I was rated at 74.35, Cycle II at 86.85, and Cycle III at 91.02. demonstrates a rise in student creativity. Cycle I to Cycle III saw an increase of 16.67. Students' creativity falls under the categories of moderate creativity in cycle I, high creativity in cycle II, and high creativity in cycle III.Kata kunci: Creativity, Project Based Learning, Science.